Aspects of the International Banking Safety Net - Johnson, G. G.; Abrams, Richard K. (Washington, D.C. : International Monetary Fund, 1983)
This paper focuses on one aspect of banks' willingness and ability to continue international intermediation. It provides a qualitative assessment of the strengths and weaknesses of existing safeguards for the continuity of international mediation by banks.
Bibliography: p. 36.
osc 9/8/17
Loans
Keywords: Banks and Banking, International; Loans, Foreign